Mendelian randomization analysis reveals causal relationship between allergic diseases and influenza - Hui Li, BSc; Yanping Zong, BSc; Lei He, BSc; Yujie Sun, BSc; Weibing Shi, MD; Jinchen Guo, MD (World Allergy Organization Journal)
Background: Allergic diseases and influenza share similar genetic backgrounds and pathophysiological mechanisms. Observational studies have established a correlation between these 2 conditions; however, the precise direction of the causal relationship remains unclear. This Mendelian randomization (MR) study aims to evaluate the causal relationship between allergic diseases and influenza. Materials and methods: This study utilized summary statistical data from genome-wide association studies (GWAS) and employed the two-sample MR method to comprehensively analyze the causal relationships between allergic diseases (asthma, hay fever, eczema), atopic dermatitis (AD), hay fever or allergic rhinitis (AR), and different types of influenza (including all influenza, regular influenza excluding pneumonia, and severe influenza that encompasses both influenza and pneumonia) using genetic factors as instrumental variables. The analysis primarily relied on the inverse variance weighted random effects model (IVW-RE). Results: The IVW-RE analysis revealed significant correlations between allergic diseases (asthma, hay fever, or eczema) and both all influenza and severe influenza (influenza and pneumonia). Additionally, AR (hay fever or allergic rhinitis) was associated with both all influenza and regular influenza (excluding pneumonia). Furthermore, a significant correlation was found between asthma and severe influenza (influenza and pneumonia). However, there is no evidence to support a causal relationship between AD and influenza. Conclusion: The results of this MR study support a causal relationship between allergic diseases, asthma, and influenza, including severe influenza. This finding suggests that allergic diseases and asthma are significant risk factors for influenza. Additionally, this study provides high-quality causal evidence that can inform clinical practices aimed at preventing the onset of influenza, particularly in populations with respiratory allergies and asthma.